Pengadaan Tanah untuk Kepentingan Umum Perspektif Konsep Keadilan Thomas Aquinas - Safarinda, Rima Dea; Anantha, Akmal Ricko Fery; Prakoso, Bhim; Efendi, Aan (Jurnal Ilmiah Penegakan Hukum, 2025)
This This paper analyzes the legal provisions relating to land acquisition for the public interest by using the perspective of the concept of justice according to Thomas Aquinas. This normative juridical method study illustrates that the nomenclature of land acquisition for the public interest contained in Law Number 2 of 2012 concerning Land Acquisition for Development in the Public Interest and has been revised in part in Law Number 6 of 2023 concerning Job Creation has not embodied the concept of justice echoed by Thomas Aquinas in the fulfillment of one's rights. This study concludes that the nomenclature of land acquisition for the public interest has a critical note regarding commutative justice (Justitia commutative), namely the legal provisions regarding the assumption that the community agrees to the use of their land contained in the nomenclature of land acquisition for the public interest, even though the person concerned was not present in the public consultation session. This is not in accordance with Thomas Aquinas' concept of justice, which emphasizes the equality of a person as a holder of land rights that must be fulfilled.